Pengembangan Media Flash Card Filum Echinodermata dan Filum Porifera - Indah Saskia; Eko Wulandari; Rivo Yulse Viza (Pendidikan Biologi STKIP YPM Bangko, 2021)
This research is motivated by the absence of learning media such as Flash Card, the learning media used in schoolis only in the form of textbooks. The textbook used presents a slightly colored appearance, the material is not detailed and the images are few. The material of Phylum Echinodermata and Phylum Porifera doesn’t present the characteristics and sample images of each species of each class, from Phylum Echinodermata and Phylum Porifera. This study aims to describe the process of developing Flash Card media for Phylum Echinodermata and Phylum Porifera as Integrated Science learning media for class VII SMP Negeri 27 Merangin. This research is a development research that using 4-D which includes the stages of define, design, develop and disseminate. The subjects of this study consisted of 7 validators consisting of 5 STKIP YPM Bangko lecturers and 2 Integrated Science teachers at SMP Negeri 27 Merangin. This research instrument uses a validation questionnaire, then this data is analyzed by descriptive analysis. Based on the results of this study, a valid Integrated IPA Flash Card was produced. The resulting Integrated Science Flash Card was declared very valid by the validator both from the aspects of the feasibility of content, language, presentation and graphics with an average validity value of 94%. So it can be concluded that the Flash Card of Phylum Echinodermata and Phylum Porifera have been declared valid.